Pengaruh Gerakan Literasi Terhadap Keterampilan Membaca Di UPT SD Negeri 064036 - Fitri Agustia; Mia Aulina Lubis (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2023)
Reading is the most basic ability as a provision for learning everything, in reading literacy means a form of learning that is very interesting and important for students so that a lesson is easy to understand when carrying out reading, writing and communicating activities. This study aims to find out whether the literacy approach can affect the reading skills of students in grades III, IV, and VI of SD Negeri 064036 Medan City District. Medan. in this era the author also sees that in such a rapid development of the era everyone must have a passion for reading and writing. in elementary school reading ability plays a crucial role, because without it the students will experience learning difficulties at that time and in the future. The author also sees that nowadays there are many people who are lazy to read especially the lack of reading culture in the environment where we live. The method used in the application of this program activity uses the casework method through the general intervention stage which consists of Engagement Intake Contract, Assessment, planning/Planning, intervention, evaluation, Termination.The result of this activity is that students understand and know the contents of the book they are reading, increasing their interest in reading better